2015
DOI: 10.1038/nature14230
|View full text |Cite
|
Sign up to set email alerts
|

The fine-scale genetic structure of the British population

Abstract: Summary Fine-scale genetic variation between human populations is interesting as a signature of historical demographic events and because of its potential for confounding disease studies. We use haplotype-based statistical methods to analyse genome-wide SNP data from a carefully chosen geographically diverse sample of 2,039 individuals from the United Kingdom (UK). This reveals a rich and detailed pattern of genetic differentiation with remarkable concordance between genetic clusters and geography. The regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

56
622
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 489 publications
(682 citation statements)
references
References 33 publications
56
622
4
Order By: Relevance
“…2008; Leslie et al. 2015). However, this clear geographic signal was somewhat unexpected for a wind‐pollinated, pioneer plant with high potential for dispersal, and especially in A. artemisiifolia , which has also experienced extreme migration and population admixture in the recent past.…”
Section: Discussionmentioning
confidence: 99%
“…2008; Leslie et al. 2015). However, this clear geographic signal was somewhat unexpected for a wind‐pollinated, pioneer plant with high potential for dispersal, and especially in A. artemisiifolia , which has also experienced extreme migration and population admixture in the recent past.…”
Section: Discussionmentioning
confidence: 99%
“…13 The aim of this study was to investigate fine-scale Italian population genetic substructure. We used both the large single-nucleotide polymorphism (SNP) data set, which we collected from a wellcharacterized Italian sample, and the most recent haplotype-based population genetic algorithms, such as fineSTRUCTURE, 14 which are able to provide finer resolution of the genetic structure of populations, as was shown for the UK population by Leslie et al 15 Specifically, our aims were to test the feasibility of identifying differences at the microregional level within Italy, to compare and quantify the contributions of populations from Europe and the Mediterranean basin to the genetic composition of the Italians and to explore the historical events that led to the observed high genomic variability within Italy. Several analytical approaches were combined to obtain a complete portrait of 'the Italian genome', and to test the robustness of our results across different methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has not been documented that this is sufficient to obviate association or linkage disequilibrium between mtDNA SNPs and specific gDNA clusters. Extensive gDNA micro-scale heterogeneity has been documented in the UK 21 and Western France 27 and admixture has been an important factor in the accretion of the present-day genomic variation of Europe 22,28 . The UK study 21 showed that this is not just a result of recent demic changes; however, recent migrations may lead to widespread 2GLD.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of such a stratification on disease association, will depend on the admixture structure of the particular population, the population history, epidemiology and genetic epidemiology of the disease, as well as the number of persons included in the study. The extensive fine-scale heterogeneity of gDNA and significant admixture documented in the UK 21 and Europe 22 further increase the risk of spurious false positive associations, if the mtDNA/gDNA interaction is not corrected phenomenon for in association studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation